Banded versus non-banded sleeve gastrectomy: a systematic review and meta-analysis - Chaouch, Mohamed Ali; Yang, Wah; Gouader, Amine; Krimi, Bassem; Carneiro da Costa, Adriano; Pourcher, Guillaume; Oweira, Hani (Medicine, 2023)
Background: - Laparoscopic banded sleeve gastrectomy (LBSG) has been compared to laparoscopic sleeve gastrectomy (LSG) in terms of anthropometric results and postoperative complications, which are controversial. This systematic review and meta-analysis aimed to compare the safety and efficacy of LBSG and LSG. Methods: - We performed a systematic review with meta-analysis according to preferred reporting items for systematic review and meta-analysis 2020 and assessing the methodological quality of systematic review 2 guidelines. We included studies that systematically searched electronic databases and compared LBSG with LSG conducted until August 10, 2021. Results: - The literature search yielded 8 comparative studies. Seven hundred forty-three patients were included: 352 in the LBSG group and 391 in the LSG group. LBSG group allowed greater anthropometric parameters (body mass index [BMI] after 1 year (mean difference [MD] = −3.18; 95% CI [−5.45, −0.92], P = .006), %EWL after 1 year (MD = 8.02; 95% CI [1.22, 14.81], P = .02), and %EWL after 3 years (MD = 10.60; 95% CI [5.60, 15.69], P < .001) and similar results with LSG group in terms of operative time (MD = 1.23; 95% CI [−4.71, 7.17], P = .69), food intolerance (OR = 1.72; 95% CI [0.84, 3.49], P = .14), postoperative vomiting (OR = 2.10; 95% CI [0.69, 6.35], P = .19), and De novo GERD (OR = 0.65; 95% CI [0.34, 1.26], P = .2). Nevertheless, major postoperative complications did not differ between the 2 groups. Conclusions: - This systematic review and meta-analysis comparing LBSG and LSG concluded that banding sleeve gastrectomy (SG) may ensure a lower BMI and %EWL after 1 year of follow-up, and a significant reduction in %EWL after 3 years of follow-up. There is no evidence to support LBSG in vomiting, de novo GERD, food intolerance, or operative time.